An overview of records management: the African experience. Issue 1 (1st December 2022) - Wamukoya, Justus
Abstract : This article is part of a contribution to honour Professor Justus Wamukoya, one of the leading records and archival practitioners and academics in Africa. The article started as a book chapter that Prof. Wamukoya had contributed to a proposed book meant to be published by professional colleagues at the University of Botswana during the four years that Prof Wamukoya spent with them. Unfortunately, the publication of the book was overtaken by events and interest in completing the work waned over time. However, Prof. Wamukoya's chapter has been converted into an article that is now being published as a tribute to remember him and his passion for the profession. The article looks at records management development in Africa and challenges and constraints that hinder development of records management in Africa. It also presents examples of some case studies in African governments aimed at improving records management. Much of the information used in this paper is from general literature and personal experience of the author having witnessed these developments during his years as a practitioner and academic.